2002
DOI: 10.1002/bem.103
|View full text |Cite
|
Sign up to set email alerts
|

Decreased DNA repair rates and protection from heat induced apoptosis mediated by electromagnetic field exposure

Abstract: In this study, we demonstrate that electromagnetic field (EMF) exposure results in protection from heat induced apoptosis in human cancer cell lines in a time dependent manner. Apoptosis protection was determined by growing HL-60, HL-60R, and Raji cell lines in a 0.15 mT 60 Hz sinusoidal EMF for time periods between 4 and 24 h. After induction of apoptosis, cells were analyzed by the neutral comet assay to determine the percentage of apoptotic cells. To discover the duration of this protection, cells were grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 30 publications
1
37
0
1
Order By: Relevance
“…The mechanism of such detrimental effects of exposing to strong magnetic fields or prolonged MF treatments are unknown; however, MF may induce mutation and DNA damage in plant (Ager and Radul, 1992) and other organisms (Zmyslony et al, 2000). Robison et al (2002) also showed that electromagnetic treatments decrease DNA repair rate. On the other hand, lower seeds germination and seedlings growth can be related to overproduction of hydrogen peroxide in plant and increased lipid oxidation after exposing seeds to stronger MF or prolonged MF treatments (Podleoeny et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of such detrimental effects of exposing to strong magnetic fields or prolonged MF treatments are unknown; however, MF may induce mutation and DNA damage in plant (Ager and Radul, 1992) and other organisms (Zmyslony et al, 2000). Robison et al (2002) also showed that electromagnetic treatments decrease DNA repair rate. On the other hand, lower seeds germination and seedlings growth can be related to overproduction of hydrogen peroxide in plant and increased lipid oxidation after exposing seeds to stronger MF or prolonged MF treatments (Podleoeny et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Comet Assays-Neutral comet assays were performed as described previously (61,62) with slight modifications. 12,000 -15,000 cells from treated cultures were suspended in low-melting point agarose in PBS (Invitrogen, final concentration of 0.75%) and layered on microscope slides.…”
Section: Methodsmentioning
confidence: 99%
“…Previous study demonstrated that electromagnetic treatment decreased DNA repair rates in human cancer cell lines (Robison et al, 2002). MF could also induce plant mutation (Ager and Radul, 1992) and UV-B irradiation could produce cyclobutane dimers (CPD) and (6-4) photoproducts in plant DNA (Britt, 1996).…”
Section: Effect Of Mf-pretreatment and Uv-b Radiation On Seedling Growthmentioning
confidence: 99%